Arginina para matrizes suínas primíparas em lactação - Lemes, Marina Alves Gomes (2016)
With the emergence of new genetic lines due to intense breeding improvement on swine production in recent years, there is the need to adapt more accurately diets for the current sows, which have higher nutritional demands. The use of functional amino acids aimsto optimize the sows production and among these amino acids arginine has excelled. Arginine is involved in several important metabolic pathways, for example, it serves as a substrate forsynthesis of protein, creatine, nitric oxide, polyamines, citrulline, agmatine, ornithine, proline, and glutamate. It also helps to stimulate the secretion of some hormones such as insulin, prolactin, and growth hormone.As arginine plays such important roles, its supplementation has been suggested in lactation feed once it may enhance the development of the mammary gland and milk nutritional profile, thus, providing a better piglet development.Thus, the objective was to evaluate the effect of lactation feed supplementation with L-Arginine on the productive performance of primiparoussows and their respective litter.One hundred forty sows from the same genetic lineage on a commercial farm, located in the city of Oliveira, MG were used in this study, in a completely randomized design with five treatments: control diet without amino acid supplementation and four diets with increasing levels of L-Arginine supplementation (containing 98.5% purity) - 0.5, 1.0, 1.5, and 2.0%. Each treatment hadtwenty-eight swine sows, and the experimental unit was the sowand its litter.It was used ‘on top’ amino acid supplementation.All data was submitted to variance analysis using the SAEG Software: version 9.1 (SAEG, 2005).The data relating to days of lactation were compared by Tukey test (5%). L-Arginine supplementation levels in lactation feed did not influence (P>0.05) average daily feed intake, body condition variables, and blood parameters of the sows (urea, creatinine, and non-esterified fatty acids) as well as it did not affect the dry matter, crude protein, and amino acid profile of milk and the litter performance. There was effect (P<0.05) of days of lactation on the percentage of crude protein and amino acids in milk, which reduced througout the days of lactation. The L-Arginine supplementation on the lactation diet at levels of 0.5, 1.0, 1.5, and 2.0% did not influence the sow and its respective litter performance.